It's About Time, Part II: Does Time Poverty Contribute to Inequitable College Outcomes by Gender and Race/Ethnicity? - Claire Wladis; Alyse C. Hachey; Katherine M. Conway (SAGE Publishing, 2024)
Existing research demonstrates gender- and race/ethnicity-based inequities in college outcomes. Separately, recent research suggests a relationship between time poverty and college outcomes for student parents and online students. However, to date, no studies have empirically explored whether differential access to time as a resource for college may explain differential outcomes by gender or race/ethnicity. To address this, this study explored the relationship between time poverty, gender or race/ethnicity, and college outcomes at a large urban public university with two and four year campuses. Time poverty explained a significant proportion of differential outcomes (retention and credit accumulation) by gender and race/ethnicity. More time-poor groups also dedicated a larger proportion of their (relatively limited) discretionary time to their education, suggesting that inequitable distributions of time may contribute to other negative outcomes (e.g., reduced time for sleep, exercise, healthcare). This suggests that time poverty is a significant but understudied equity issue in higher education.